Prueba empírica de un modelo de calidad de vida. (2015)
This work was proposed to establish a correlative model to discuss the importance of other variables in the investigation of the quality of life. Once the relationship between the factors derived from the literature review were specified, a crosssectional study was carried out with a nonrandom sample of 245 students. When the validity and reliability of the instrument measured was obtained: life satisfaction, expected capacities, expectations of opportunity, trust relationships, perceptions of fairness, valuing the environment, rules of context and perceived resources, a structural model was contrasted [X2 = 12,35 (12 gl) p = 0.000; GFI = 0.975; RMR = 0.000] in which the perceived availability of resources indirectly correlated to life satisfaction through context rules (γ = 0.52). The results were compared with the findings reported in the state of knowledge.